The evolution of the world trade web - Giorgio Fagiolo; Javier Reyes; Stefano Schiavo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
This paper employs a weighted network analysis to study the empirical properties of the world trade web and their evolution over time. We show that most countries are characterized by weak trade links; yet, there exists a group of countries featuring a large number of strong relationships, thus hinting to a core-periphery structure. Also, better-connected countries tend to trade with poorly-connected ones, but are also involved in highly-interconnected trade clusters. Furthermore, rich countries display more intense trade links and are more clustered. Finally, all network properties are remarkably stable across the years and do not depend on the weighting procedure.
Keywords: F10; D85; 330; networks; World trade web; international trade; weighted network analysis; integration; trade openness; globalization; Internationale Wirtschaftsbeziehungen; Internationale Wirtschaft; Netzwerk; Internationale Handelspolitik; Schätzung; Außenwirtschaftstheorie; Welt